Luring the Lurkers: Increasing Participations in the Online Discussions of a Blended Learning Course - Chuah, Kee-Man (Universiti Malaysia Sabah, 2014)
Despite the popularity of online discussion threads, there is a growing concern on the lack of participation among the learners. The number of responses in discussion threads is dropping and has discouraged healthy exchanges of ideas among the learners. Most learners tend to be online lurkers who rarely provide feedback although they are rather active in reading others’ posts. In this study, a few techniques were employed in the online discussion threads of a blended learning course on academic reading and writing in order to promote lurkers’ participations. Discussion topics were posted throughout the 14-week course offered at Universiti Malaysia Sarawak (UNIMAS) using different techniques in order to supplement the activities conducted in faceto- face classes. Based on the discourse analysis of responses posted by 122 participants, three techniques were noted to be successful in luring the lurkers to be more active in the discussion, which include the use of a comic strip as a topic starter, incorporation of social talks and instructor’s frequent intervention. At the end of the course, semi-structured interviews were conducted to ind out the lurkers’ overall perceptions on their behaviour in online discussion. The analysis revealed that the number of responses is not directly incremental to the mastery of the subject matter. However, it is the learner’s sense of belonging to the online community that persuaded them to be more active in sharing their ideas. Thus, cohesion and deeper scrutiny of the discussion topic are largely facilitated by the cultivation of social elements in each discussion.